The relationship between the current knowledge’s satisfaction of disaster preparedness and the practice of family emergency planning - Elsi D. Hapsari; Salma Nur Azizah; Diki Nanang Surahman; Sutono Sutono; Satoko Watanabe; Jihan Siti Lathifa Luthfiyah (Jurnal Keperawatan Padjadjaran, 2025)
Background: Since the 2020 version, the content of family emergency planning (FEP) has been included in the Indonesian Maternal and Child Health (MCH) handbook.  However, there is still limited information on whether pregnant women, especially those who are living in disaster-prone areas like Yogyakarta Province, practice it in their day-to-day lives.  Purpose: to analyse the relationship between the current knowledge’s satisfaction of disaster preparedness and the practice of FEP among pregnant women based on the MCH handbook.  Methods: A quantitative descriptive survey with a cross-sectional design was applied in this study.  Data collection was conducted between March and September 2024 using three questionnaires, which included demographic data, current knowledge’s satisfaction with disaster preparedness, and practice of FEP.  The samples were 277 pregnant women.  Data were analysed with a chi-square test and Cramer’s V test Results: Most of respondents reported of having quite satisfied (43.32%) with their current knowledge of disaster preparedness.  As many as 135 respondents (48.73%) reported practicing FEP, but only 35.56% of them completed the practice.  There is a significant relationship between the satisfaction of current knowledge about disaster preparedness with the practice of FEP, but the association is weak (p=0.04, Cramer’s V=0.04).  Conclusions:  The current knowledge’s satisfaction with disaster preparedness and the practice of FEP has a significant relationship, but the association is weak.  Policymakers need to develop disaster preparedness and FEP strategies based on the findings in the field and the identification of barriers.  Health care professionals should improve pregnant women’s FEP and ensure that they practice it in their daily lives through various activities such mobile reminders, group education, and integration into digital platforms.